Ocorrência e períodos de interferência de plantas daninhas na cultura de feijão-caupi em cultivares de porte semiereto e semiprostrado - Castro, Thaís Santiago (2017)
The objective of this work was to determine the occurrence and periods of weed interference in cowpea cultivars in semi-erect and semi-prostrate cultivars. Two experiments were carried out in the experimental field of the Federal University of Roraima, Campus Cauamé, municipality of Boa Vista-RR, were conducted in the period from August to October 2016 with BRS Guariba cowpea cultivars semi-erect and BRS Aracê semi-prostrate. The experimental design was in randomized blocks, with four replications, in a 7x2 factorial scheme consisting of 7 control periods x 2 types of weed management. The control and coexistence periods for cultivars BRS Guariba and BRS Aracê consisted respectively of 0, 0-8, 0-16, 0-24, 0-32, 0-45, 0-60 DAE and 0, 0-8, 0-16, 0-24, 0-32, 0-45, 0-64 days after emergency (DAE). The composition of the weed community was evaluated in order to obtain phytosociological parameter (relative importance), as well as the production components of cowpea (Final stand, Number of pods per plant, Bean length, 100 grain mass and grain yield). The weeds that stood out in coexistence with both cultivars were Digitaria horizontalis, Cenchrus echinatus and Desmodium tortuosum. The interference caused by weeds in coexistence with the crop influenced negatively the number of pods per plant and productivity. Competition throughout the cycle reduced productivity by up to 39.81% for cv. BRS Guariba and 37.27% for cv. BRS Aracê. Considering 5% productivity losses for BRS Guariba and BRS Aracê cowpea cultivars, the period prior to interference (PAI) were 9 and 15 days after emergence (DAE), respectively; The total interference prevention period (PTPI) of 41 and 32 DAE and the critical period of interference prevention (PCPI) of 9 to 41 DAE and 15 to 32 DAE, respectively. The cv. BRS Aracê of semi-prostrate bearing presented competitiveness with weeds, requiring a shorter control period to express maximum productivity.